Fantômes et fantasmes de l’histoire dans Anima de Wajdi Mouawad - Valenti, Simonetta (Ponti/Ponts, 2021)
Populated by different phantoms, Anima, Wajdi Mouawad’s second novel, presents a universe of violence and hatred, in which the hero, Wahhch Debch, tries to discover his wife’s murder, in a desperate journey through North America. But soon the detective novel becomes a novel of introspection which changes again into an historical novel, manifesting thus the writer’s ability to revisit and transform the three traditional genres into a new, passionate masterpiece.